Association of Fetuin-A with Incident Diabetes in Community-Living Older Adults: The Cardiovascular Health Study - Ix, Joachim H. (2012)
BACKGROUND: The liver secreted protein fetuin-A induces peripheral insulin resistance in vitro. In a pilot study, we observed that higher fetuin-A levels were associated with diabetes in older persons. However, this finding has not been confirmed in large cohorts. We sought to confirm the association of fetuin-A with incident diabetes in older persons, and to determine if the association differs by age, sex, and race, and among persons with CVD. METHODS AND RESULTS: Among 3,710 community-living individuals aged ≥ 65 years without diabetes at baseline, serum fetuin-A was measured in serum collected in 1992–93. Participants were followed for 10.6 years (median) for incident diabetes. Cox regression models evaluated the association of fetuin-A with incident diabetes. Interaction terms evaluated heterogeneity by age, sex, race, and CVD. Mean age was 75years, 60% were female, 15% were black, and 16% had CVD. Mean fetuin-A concentrations were 0.47 ± 0.10 g/L. During follow-up, 305 incident diabetes cases occurred. Each 0.10g/L (SD) greater fetuin-A was associated with 19% higher risk of diabetes (HR 1.19; 95%CI 1.06–1.33) after adjusting for demographics, life-style factors, albumin, kidney function, and CVD. Further adjustment for potential mediators (body mass index, waist circumference, hypertension, lipids, and CRP) moderately attenuated the association (HR 1.13; 95% CI 1.00–1.28). Results were similar by sex, race, and CVD status, but were stronger in persons <75 years old (P-interaction 0.01). CONCLUSIONS: Higher fetuin-A is associated with incident diabetes in older persons, irrespective of sex, race, or prevalent CVD status. The association may be attenuated in those aged ≥ 75 years.